Experimental validation of the solid state substation with embedded energy storage concept - Klumpner, Christian; Rashed, Mohamed; De, Dipankar; Kulsangcharoen, Ponggorn; Patel, Chintanbai; Asher, Greg (2016)
This paper proposes the concept of integrating the energy storage within a Medium Voltage to Low Voltage solid state substation in order to provide new features compatible with the requirements from future more intelligent grids. The principles for the system development are presented and the role of each subsystem is explained. The experimental evaluation of the 1.9kVrms/25kVA substation with 1.5MJ of supercapacitor storage consists of subsystem tests showing the waveform quality, step transients as well as system tests of the efficiency, ride-through and power peak shaving operation.